High-Current-Density field emission from self-heating printed carbon nanotubes. Issue 4 (2nd April 2016) - Wang, Qilong; Yu, Cairu; Di, Yusong; Zhu, Zhuoya; Zhang, Xiaobing; Li, Chen; Lei, Wei
ABSTRACT: High-current-density field emitters are considered as the potential and necessary components for compact high definition x-ray sources and high-power cold cathode microwave amplifiers. In this report, high-current-density field emission from self-heating printed carbon nanotubes is introduced. Large emission current causes large heat that increases the temperature of the emitters. The temperature is estimated to be more than 1600 K. Localized surface field and high temperature both drive more electrons escaping from the emitters, and the maximum current density is larger than 2.7 A/cm 2 that will satisfy the need of most vacuum electron devices including x-ray sources and microwave electron devices.